EFFECT OF CANDESARTAN ON PARAMETERS OFDAILYBLOOD PRESSURE IN PATIENTS WITH CHRONIC KIDNEYDISEASE ON HEMODIALYSIS - V. A. Vizir; О. G. Ovska; A. S. Sadomov (Український Журнал Нефрології та Діалізу, 2017)
Introduce.Advances of normal blood pressure in patients on program hemodialysis presented a serious problem related disciplines. For verification hypertension used routine blood pressure measurement and ambulatory monitoring to control the pressure in interdialytic time, which is an important predictor of cardiovascular events among these patients.